Da pedagogia do oprimido ao direito do oprimido: uma noção de direitos humanos na obra de Paulo Freire - Góes Junior, José Humberto de (2008)
The apparent distinctiveness of the education theme in Paulo Freire's work is replaced by a careful examination of the author's thinking, for an obvious concern with the transformation of society. According to this aspect, you can say that Paulo Freire has, as the basis of his philosophical structure, the mechanisms construction to surmount social inequalities, to which is summed up into promoting human dignity in all circumstances in which it is coupled, so that you assert the genuine meaning of the term. Putting in doubt the pedagogical environment would therefore be an epigraph to think of a detrimental reality modification for human rights and the humanity condition, which is expressed in an oppressor/oppressed relation set by Freire. It is impossible unravel the debate about the dignity and human rights of a democracy and citizenship conception, in the course of his writings on social emancipation, Freire theorizes and builds, on a new democratic canons, the formulation of a political culture of human rights defense. Therein, to establish the focus of this work as being the Paulo Freire's relationship with the human rights debate, it is contested the science and epistemology that the theories of traditional law are based on, so that we can connect the legal phenomenon to the ethical base that was set apart in Modernity and overcome the fixed models of thought within the law, conditions able to characterize the oppression and vulnerable social groups in Brazil are pointed out, it is discussed the hegemonic and counter-hegemonic formats of democracy and citizenship, bound for, overcoming the liberal elements that mark his instrumentalist modes of expression, to harness them toward human rights, including a way to think them through an ethic of justice and equal rights, an release ethic. To do so, the written provisions are only taken up on into five major Paulo Freire's works: Education and Practice of Freedom; Pedagogy of the Oppressed; Letters to Guinea-Bissau; Pedagogy of Hope, and Pedagogy of Autonomy.